PEMBINAAN KECAMATAN KAMPAR TIMUR OLEH PEMERINTAH DAERAH KABUPATEN KAMPAR - Yonry, Gery Ari; Yusri, Ali (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Gery Ariyonri "Development of Eastern District of Kampar Kampar District by theGovernment". Tier One Degree Thesis, Faculty of Social and Political Sciences, Universityof Riau in 2014 guided by Drs. Yusri Ali, MSThis study aims to determine why the task execution Kampar regency administration infostering government Apparatus Eastern District of Kampar do not run well and look at theobstacles faced by the district administration in fostering Apparatus Eastern District ofKampar.The method used in this research is by using a qualitative approach. Types and sources ofdata in this study were obtained from Primary Data and Secondary Data. Collecting data inthis study conducted in observation, documentation and interviews. Informant research is PRKampar district, sub-district and sub-district secretary, and several community leadersKampar East. Informants in this study determined purposive sampling, and data analysistechnique used is descriptive qualitative.Field findings the authors conclude that the Kampar District Government has done incoaching but coaching pelasanaanya conducted Kampar regency administration is not donecontinuously and regularly. The process of coaching is done Kampar regency administrationby providing guidance, give direction, provide training and education, providing instructionand provide manuals to the Government Apparatus Eastern District of Kampar. However, inpractice based on the research results of the local government district of KamparExperiencing the absence of constraints operating costs of the district continues to provideguidance and regular, and therefore coaching is done is not going well.Keywords: Guidance, district, sub-district head